Antimicrobial Diterpenes: Recent Development From Natural Sources - Saha, Poushali; Rahman, Fahad Imtiaz; Hussain, Fahad; Rahman, S. M. Abdur; Rahman, M. Mukhlesur (Frontiers in Pharmacology, 2022)
Antimicrobial resistance has been posing an alarming threat to the treatment of infectious diseases over the recent years. Ineffectiveness of the currently available synthetic and semisynthetic antibiotics is leading the researchers to discover new molecules with potent antimicrobial activities. To overcome the emerging antimicrobial resistance, new antimicrobial compounds from natural sources might be appropriate. Secondary metabolites from natural sources could be the prospective candidates in the development of new antimicrobial agents with high efficacy and less toxicity. Among the natural secondary metabolites diterpenoids are of crucial importance because of their broad spectrum of antimicrobial activity which has put it in the center of research interest in the recent years. The present work is aimed at reviewing recent literatures regarding different classes of natural diterpenes and diterpenoids with significant antibacterial, antifungal, antiviral and antiprotozoal activities along with their reported structure activity relationships. The review has been carried out focusing on relevant literatures published in last five years following the PRISMA guidelines. A total number of 229 diterpenoids from various sources notably plants, marine species and microorganisms are summarized in this systematic review including their chemical structures and significant antimicrobial activities together with their reported mechanism of action and structure activity relationships. The outcomes herein would provide the researchers with new insights to find out new credible leads and to work on their synthetic and semisynthetic derivatives to develop new antimicrobial agents.